The pharmacological properties and corresponding mechanisms of farrerol: a comprehensive review - Xiaojiang Qin; Xinrong Xu; Xiaomin Hou; Ruifeng Liang; Liangjing Chen; Yuxuan Hao; Anqi Gao; Xufeng Du; Liangyuan Zhao; Yiwei Shi; Qingshan Li (Taylor & Francis Group, 2022)
Context Farrerol, a typical natural flavanone isolated from the traditional Chinese herb 'Man-shan-hong' [Rhododendron dauricum L. (Ericaceae)] with phlegm-reducing and cough-relieving properties, is widely used in China for treating bronchitis and asthma. Objective To present the anti-inflammatory, antioxidant, vasoactive, antitumor, and antimicrobial effects of farrerol and its underlying molecular mechanisms. Methods The literature was reviewed by searching PubMed, Medline, Web of Knowledge, Scopus, and Google Scholar databases between 2011 and May 2021. The following key words were used: 'farrerol,' 'flavanone,' 'anti-inflammatory,' 'antioxidant,' 'vasoactive,' 'antitumor,' 'antimicrobial,' and 'molecular mechanisms'. Results Farrerol showed anti-inflammatory effects mainly mediated via the inhibition of interleukin (IL)-6/8, IL-1β, tumour necrosis factor(TNF)-α, NF-κB, NO, COX-2, JNK1/2, AKT, PI3K, ERK1/2, p38, Keap-1, and TGF-1β. Farrerol exhibited antioxidant effects by decreasing JNK, MDA, ROS, NOX4, Bax/Bcl-2, caspase-3, p-p38 MAPK, and GSK-3β levels and enhancing Nrf2, GSH, SOD, GSH-Px, HO-1, NQO1, and p-ERK levels. The vasoactive effects of farrerol were also shown by the reduced α-SMA, NAD(P)H, p-ERK, p-Akt, mTOR, Jak2, Stat3, Bcl-2, and p38 levels, but increased OPN, occludin, ZO-1, eNOS, CaM, IP3R, and PLC levels. The antitumor effects of farrerol were evident from the reduced Bcl-2, Slug, Zeb-1, and vimentin levels but increased p27, ERK1/2, p38, caspase-9, Bax, and E-cadherin levels. Farrerol reduced α-toxin levels and increased NO production and NF-κB activity to impart antibacterial activity. Conclusions This review article provides a theoretical basis for further studies on farrerol, with a view to develop and utilise farrerol for treating of vascular-related diseases in the future.